Comparative study to assess functions of NGO and Government managed anganwadi centres of Ahmedabad city, Gujarat, India - Makadia, Khushbu D.; Barot, Divya B.; Shah, Yash R. (International Journal Of Community Medicine And Public Health, 2016)
Background: ICDS scheme is one of the world’s largest and unique programs for early childhood development. With a commitment towards public private partnership, ICDS approached identified NGOs to deliver ICDS services and to operationalize the anganwadi centres (AWCs). Objectives of the study were to assess the functioning of NGO and Govt. managed AWCs in terms of infrastructure, supplies and utilization and Identify the operational gap. Methods: Cross sectional study was carried out in 20 randomly selected AWCs of Ahmedabad city. 50% NGO managed and 50% Govt. managed AWC were observed and anganwadi workers were interviewed. Statistical analysis Data entry and analysis was done in Microsoft Excel and chi square was used as test of significance. Results: Most of AWCs were running as a part of house on rent. Proper way of display of information was found more among NGO managed AWCs (80%). Malnourished children were found more in Govt. managed AWCs than NGO managed. This difference was statistically significant (p<0.05). Immunization status of children of NGO managed AWCs was better than Govt. managed AWCs and difference in immunization coverage was found statistically significant (<0.05). Conclusions: Services are better in NGO managed AWCs in comparison to Govt. both in terms of quality and quantity.